Implementation of Electronic Seal Cargo at Cikarang Dry Port to Support National Logistics System - Adiyuna, Natabita Ayum; Novel, Nurillah Jamil Achmawati; Kurniawan, Komang Sandhi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This study discusses the implementation of Electronic Seal (E-Seal) Cargo at Cikarang Dry Port as an effort to support container cargo security in Indonesia's Sistem Logistik Nasional (Sislognas). This research also examines the role of Cikarang Dry Port as a key logistics infrastructure in facilitating the entry of international cargo goods into Indonesia, with the implementation of E-Seal on their fleet as a step to support the achievement of Sislognas targets. The research method of this article uses a descriptive qualitative method. The data obtained is used to understand how the implementation of the use of e-seal at cikarang dry port. The results of this study are a description of the types of e-seal devices used, the flow of e-seal use at cikarang dry port and an analysis of the level of damage to E-seal devices.